Modification and application of “zero-line” incision design in total endoscopic gasless unilateral axillary approach thyroidectomy: A preliminary report - Wang, Huiling; Liu, Rui; Zhang, Chaojie; Fang, Qian; Zeng, Zheng; Wang, Wanlin; You, Shuo; Fang, Meng; Dingtian, Jinhao (Frontiers in Surgery, 2023)
Introduction: Gasless unilateral trans-axillary approach (GUA) thyroidectomy has witnessed rapid development in technologies and applications. However, the existence of surgical retractors and limited space would increase the difficulty of guaranteeing the visual field and disturb safe surgical manipulation. We aimed to develop a novel zero-line method for incision design to access optimal surgical manipulation and outcomes. Methods: A total of 217 patients with thyroid cancer who underwent GUA were enrolled in the study. Patients were randomly classified into two groups (classical incision and zero-line incision), and their operative data were collected and reviewed. Results: 216 enrolled patients underwent and completed GUA; among them, 111 patients were classified into the classical group, and 105 patients were classified into the zero-line group, respectively. Demographic data, including age, gender, and the primary tumor side, were similar between the two groups. The duration of surgery in the classical group was longer (2.66±0.68 hours) than in the zero-line group (1.40±0.47 hours) (p<0.001). The counts of central compartment lymph node dissection were higher in the zero-line group (5.03±3.02 nodes) than that in the classical group (3.05±2.68 nodes) (p<0.001). The score of postoperative neck pain was lower in the zero-line group (1.0±0.36) than that in the classical group (3.3±0.54) (p<0.05). The difference in cosmetic achievement was not statistically significant (p>0.05). Conclusion: The "zero-line" method for GUA surgery incision design was simple but effective for GUA surgery manipulation and worth promoting.